The reality of Islamic Takaful Insurance in the light of the Algerian Insurance Law: Analytical reading of the excusive decree N˚09/13 - - Marouf, Sanaa (The International tax journal, 2025)
In this research paper, we attempt to address the most important differences between conventional insurance and Takaful (Islamic) insurance, highlight the most important points of difference between them, and to shed light on one of the most important decrees included in the Algerian insurance law, which establishes the creation of mutual insurance companies without discrimination between one sector and another. The observer of the content of their rules may worry whether they really seek to apply Islamic insurance. In the end we concluded that it is not possible to establish a system for Islamic companies’ insurance through the Algerian insurance law, as it differs in many points with the conditions set by the jurisprudence scholars for the establishment of Islamic Takaful insurance companies.